Pemberdayaan Masyarakat melalui Kelompok Wanita Tani di Jorong Pulau Air Barat Nagari Tandikat Kecamatan Patamuan Kabupaten Padang Pariaman - Putri, Adellia; Lanin, Dasman (Lembaga Yasin AlSys, 2025)
Community empowerment, particularly of rural women, plays a vital role in enhancing both economic and social well-being. However, limited access to resources, training, and markets remains a key obstacle to fully realizing the potential of women farmers. This study aims to analyze the implementation of community empowerment through Kelompok Wanita Tani (KWT, or Women Farmers’ Groups) in Jorong Pulau Air Barat, Nagari Tandikat, Patamuan Subdistrict, Padang Pariaman Regency, by examining three main aspects: enabling (creating supportive conditions), empowering (strengthening capacity and participation), and protecting (safeguarding institutional sustainability and social solidarity). A qualitative descriptive method was employed, with data collected through observation, in-depth interviews with KWT members and village officials, and documentation of group activities. The findings reveal that the enabling aspect has been implemented through local government support and recognition, although challenges remain in post-harvest facilities and market access. The empowering aspect is reflected in improved skills, confidence, and member participation following training programs. The protecting aspect is manifested through internal group regulations, regular mentoring, and social solidarity that sustains institutional resilience. These findings affirm that group-based empowerment through KWT significantly contributes to strengthening the economic independence of rural women and reinforcing the social fabric of local communities.